Investigation on the prominence of abrupt expansion on the base pressure of an axi-symmetric body - Bashir, Musavir; Khan, Sher Afghan (Institute of Institutional Industrial Research, 2017)
This investigation presents the outcome of the tests conducted to control the base flows at supersonic Mach numbers. Also the efficiency of the flow controllers to govern the pressure in the base region in a rapidly expanded duct has been exercised. Four tiny jets of 1mm diameter are positioned at 90 intervals at a distance of 6.5 mm from the central axis of the main jet. The inertia levels of the abruptly expanded flows are 1.25, 1.3, 1.48, 1.6, 1.8, 2.0, 2.5 and 3.0. These jets are connected by an axi-symmetric circular brass tube whose cross-sectional area was 2.56, 3.24, 4.84 and 6.25 respectively. The L/D ratio of the enlarged duct was varied from 10 to 1 and NPR was varied from 3 to 11. However, the results presented were for Low Length to Diameter ratio, equal to 4. It was found that when the flow was discharged to the ducts of the given area ratios, it remained attached with the duct wall for all the inertia levels and the NPRs tested in the present case. It was found that the expansion level plays a significant role to decide the pressure at the base and its control efficacy. Whenever, the flow is over expanded, an oblique shock is formed at the nozzle lip, which in turn leads to enhancement of the pressure in the base region. The formation of the shock waves, reflection and recombination continued till the pressure becomes atmospheric. It was observed that the flow remains attached even for low length-to-diameter ratio, equal to 4. No adverse effect of back pressure was observed during the test. It was found that the micro jets can serve as controllers for the base pressure.